Examining 12-14 Age Secondary School Students’ Tendency to Violence doing Active Sport or not - AYDIN, Pelin; ERSOY, Adnan; AKTAŞ, Neslişah (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
The aim of this study was to investigate secondary school students’ tendency to violence, doing active sport or not. The sampling group of the study was consisted of 101 girls and 99 boys in the total 200 secondary school students in Kütahya city center of whose ages differs between of 12-14. In the study tendency to violence scale, developed by Göka and colleagues, was used as data gathering tool. In the evaluation of the data SPSS package program for Windows was used and after reliability of the scale was assessed One Sample Kolmogorov-Smirnov test was applied for if the obtained data was showing normal distribution and also as hypotheses tests Independent Samples t Test was applied for pairwise comparisons and One Way ANOVA test was applied for triple or more comparisons. As a result of the study there were no significant differences between students’ tendency to violence according to their ages and sport participation situations, on the other hand there were significant differences according to their class and perceived success in class. This study showed that class and perceived success in class are predictors of tendency to violence.